The politics of cross-border crime in greater China: case studies of mainland China, Hong Kong, and Macao - Lo, Shiu-hing ([Hong Kong becoming China])
Types and patterns of transborder crime in greater China -- The PRC state response at national, provincial, and local levels -- Cross-border crime and the postcolonial state in Hong Kong -- Response of the postcolonial state in Macao -- Espionage and terrorism -- Intergovernmental and regional cooperation